Inflation, operating cycle, and cash holdings - Yanchao Wang; Yu Ji; Xu Chen; Chunlei Song (China Journal of Accounting Research, 2014)
A corporate cash-holding strategy is a trade-off between the costs and benefits of holding cash. At the macrolevel, firms are inclined to adjust and optimize their cash-holding strategies in response to changes in purchasing power due to inflation. At the microlevel, the operating cycle, which indicates the speed and turnover of corporate cash flow, also influences the corporate cash-holding strategy. Firms flexibly adjust their cash-holding strategies in response to changes in the internal and external environment, which is referred to as the cash adjustment strategy. We examine these predicted relationships using a sample of listed firms in China’s stock market over the 1998–2009 period. Consistent with our predictions, the empirical results indicate a significant negative association between cash holdings and the CPI, but the relationship is reversed when the CPI reaches a certain level. There is also a U-shaped relationship between operating cycle and cash holdings, and this relationship is similarly influenced by changes in the inflation level. In examining the macroeconomic environment and microlevel firm-specific characteristics simultaneously, our findings supplement the literature on firms’ cash-holding strategies and provide theoretical and practical implications.